Psychological Problems of Learners in Learning Mathematics at Elementary Level: A Case Study - Chaurasia, Prateek (SCHOOL SCIENCE, 2015)
The present study is based on the interview of 100 students (50 boys and 50 girls) of Class VII of different CBSE schools in Varanasi district. The objective of the study was to explore the psychological factors related to the learners in learning mathematics. Is only higher order intelligence responsible for learning mathematics or are there some other factors too which are responsible for learning and non-learning of mathematics at the elementary level? Focusing on the responses of each student, we found that it is not only intelligence that influences mathematics learning, but there are some other factors too which are responsible. One of the most important factors is the psychology of the learner. It proves to be a barrier in the process of learning mathematics. There were also some major psychological factors which are responsible for the outcomes of mathematics learning in both ways positively and negatively